Development of carbon footprint quantification and reduction (cafquar) assessment tool for selected non-residential buildings - Mohammed Usman, Abdullahi (2019)
Greenhouse Gas (GHG) emission is the major consequences of industrial revolution, technology advancement and urbanisation. Building is one of the major factor of these and hence one of the major contributor to global GHG emissions. To ensure sustainable recognition in the building sector, several assessment tools were developed. Some of these tools assessed the sustainability of built environment and others quantify either water, energy, transport or greenery associated emissions hence partially capture building life cycle phase categories. The study aimed at developing an assessment tool for assessing building design emission reduction and operational emission quantification and reduction covering energy, water, transportation, waste and greenery as categories. These categories, parameters and points allocation were obtained from reviewing literatures (eleven rating systems and international standards and reports) and were divided into 27 parameters and 70 sub-parameters. The buildings are graded with star rating and together with the points allocation are distributed to a maximum of 100 Points. The performance of the tool was evaluated by considering the tool feasibility, measurability, applicability, relevancy and its compliance with international standards. These criteria were explained in the pilot and case studies assessment, comparison with other tools and consultation with stakeholders. The pilot and case study assessment cover library, four academics, and office buildings. Some of the case studies have an excellent performance grade which can be seen from their net Carbon Footprint (CFP) and carbon indexes results. This defines the tool ability to compute the net building operational GHG emission and emission density over the total floor area. These processes and criteria fulfilment describe the tools potentials in covering wider scope in relation to GHG emission in term of categories, parameters and its application to variety of non-residential buildings. It is the first tool that consider quantification of all the emission sources categories of the operational phase. The tool is useful to industries for emission quantification and reduction and to government for monitoring their industrial compliance to policies and standards.